Fisiologi Mukosiliar Bronkus - Harry Pasca Rullian; Masrul Basyar; Dewi Wahyu Fitrina (Syntax Corporation Indonesia, 2024)
One of the defense systems possessed by the respiratory tract is mucociliary transport. In order for this system to work properly, coordination of 3 components is required, namely: the motile cila, the periciliar layer (PCL), and the mucus layer. The mucus layer will catch foreign particles that enter the respiratory tract. The motile cilia will push the mucus to keep moving towards the proximal airway until it finally reaches the oropharynx and is swallowed. Cilia movement is certainly influenced by PCL which is a medium for cilia to move. In some lung diseases, this component can be impaired so that the mucociliary transport process does not work effectively.